Taxonomic study of one generic and two new species record to the flora of Pakistan using multiple microscopic techniques. Issue 4 (2nd December 2019) - Bahadur, Saraj; Ahmad, Mushtaq; Zafar, Muhammad; Gul, Saba; Ayaz, Asma; Ashfaq, Shomaila; Rubab, Saima; Shuaib, Muhammad; Ahmad, Shakil
Abstract: Recent field exploration and collections has led to the findings of several new species in Pakistan. Here we reported two new species Ajuga reptance L and Sphagneticola trilobata (L.) Prusk for the first time in Pakistan flora as these species were neither listed in any other literature nor identified before in Pakistan. These species were found as a result of taxonomic studies performed in the year 2019 in District Rawalpindi and Islamabad, Pakistan. Microscopic techniques were used for the confirmation of foliar epidermal and pollen micromorphological features. Detailed study (morphological, palynological, and foliar epidermal) was provided for the correct identification and delimitation of the species using both light and scanning electron microscopy. Morphological results were compared with the flora of Taiwan and China. Abstract : Light and scanning electron microscopic techniques were used for the correct identification of species. One generic and two new species were recorded to the flora of Pakistan for the first time. Macromorphological and micromorphological features were observed under light and scanning electron microscope for the correct identification of newly reported species.